MENINGKATKAN KAPASITAS PUBLIKASI ILMIAH DOSEN PSIKOLOGI MELALUI PROGRAM “MELEJITKAN SINTA SKOR” - Rion Nofrianda; Muhammad Ilham; Fadzlul; Hanna Widya Gultom; Mindy Maghfira; Nurul Hafizah; Annisa Dianesti Dewi (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
The community service activity titled “Boosting SINTA Scores” was carried out in response to the need to enhance the capacity of lecturers in managing academic identity and scientific publications, particularly within the Psychology Study Program, Faculty of Medicine and Health Sciences, Universitas Jambi. This hybrid-format program involved 12 active lecturer participants. Initial situation analysis revealed that most lecturers lacked a comprehensive understanding of the SINTA assessment system, citation improvement strategies, and the optimal use of academic platforms such as Google Scholar, Garuda, and SINTA itself. The program was designed using an educative and participatory approach, consisting of workshops, technical guidance, and individualized mentoring. The results showed a significant increase in participants' understanding of publication strategies and academic profile management, along with tangible improvements in the completeness and presentation of their academic profiles. Moreover, the average SINTA score among lecturers increased following the activity, indicating the effectiveness of the intervention. A sustainable discussion community also emerged from the program, encouraging collaboration and exchange of information related to scholarly publication. This initiative highlights the importance of structured and continuous interventions to support lecturers in achieving greater academic visibility and recognition through improved publication capacity and the effective use of digital technology.